Study the Trends in Energy Consumption Change for the Transport Service Sectors - Pham, Thi Hue; Nguyen, Thi Anh Tuyet (JST: Engineering And Technology For Sustainable Development, 2021)
This research analyzes energy consumption of transport service sectors in Vietnam and its changing trend in the past twenty five years using Input-Output (IO) tables and Logarithmic-mean Divisia index (LMDI) method. Energy consumption of 28 economic sectors in 1996, 2000, 2007, 2012 and 2018 are determined, of which transport service sectors always were the third or second largest energy consumer, occupied from 9 to 16% of the total energy consumption in the corresponding years. LMDI method is used to define influencing factors including: transport activity, transport structure, transport intensity and energy intensity. In these four impacts, the change of transport activity contributes the largest effect (occupied 74.3%), followed by the change of energy intensity (occupied 17.7%) of total increased share for energy consumption. Among the transport service sectors, it is found that Freight transport service by road played the mainstream role in the increase trends of energy consumption in the period of 2007-2018. In order to improve energy efficiency of the sector, investments in green transport technologies and modernization of trucks to be more efficient and eco-friendlier will be the key contributors.